"Eating is an Agricultural Act": longing for the good life - Castilho, Maria Teresa (Cadernos de Literatura Comparada, 2017)
In “The Pleasures of Eating”, Wendell Berry, a writer, poet, essayist and New Agrarian cultural critic, points out the importance of understanding the connection between food and the land, observing that “eating is an agricultural act”. This statement takes us back to 1930, when a group of intellectuals from Vanderbilt University expressed their indignation against northern industrialism and their firm belief in “an honorable peace with nature” as the basis for a good and happy life in an organized healthy and well-structured agrarian society. Berry himself has taken on this responsibility by establishing a small farm near Port Royal, Kentucky, and by sustainably working his land and writing his texts for about five decades, problematizing the importance of understanding the connection between food and land as unquestionable bases for a good life. Berry, as he himself acknowledges, is heir to some of the principles of the Agrarians of I’ll Take My Stand, and is one of the key figures in the New Agrarian Movement in American Culture, which fiercely opposes the degradation of a sustainable and healthy way of life. In his introduction to Berry’s Bringing It to the Table: On Farming and Food, Michael Pollan, one of the most active proponents of the food reform in the United States, stresses the great relevance of this writer, who, in spite of not being directly committed to a particular food movement, is someone who has inspired the rise of Food and Slow Food Movements in the United States. Actually Berry is known to many as a great inspiring reference to sustainable food movements in the United States, having thus greatly contributed to the many Food Studies programs in American higher-education institutions which started to crop up in the period around the 1990s. Nevertheless, Berry’s work and thought can be truly understood and appreciated only if we recognise the undeniable utopianism which has been feeding his hopeful prospect of an organized and well-structured agrarian society, where all might eat sustainably. As a matter of fact, if the connection between healthy and sustainable food and sustainable land was already degraded in 1989, as Berry fiercely denounced in “The Pleasures of Eating”, what then to say in 2017? To this question Wendell Berry enthusiastically keeps answering that hope is a virtue.